Molecular dynamics simulations reveal the inhibitory mechanism of Withanolide A against α-glucosidase and α-amylase - Oyewusi, Habeebat Adekilekun; Wu, Yuan Seng *; Safi, Sher Zaman; Roswanira, Abdul Wahab; Mohd Hayrie, Mohd Hatta; Kalaivani, Batumalaie (Taylor and Francis Group, 2023)
Diabetes mellitus (DM) is a global chronic disease characterized by hyperglycemia and insulin resistance. The unsavory severe gastrointestinal side-effects of synthetic drugs to regulate hyperglycemia have warranted the search for alternative treatments to inhibit the carbohydrate digestive enzymes (e.g. α-amylase and α-glucosidase). Certain phytochemicals recently captured the scientific community's attention as carbohydrate digestive enzyme inhibitors due to their low toxicity and high efficacy, specifically the Withanolides-loaded extract of Withania somnifera. That said, the present study evaluated in silico the efficacy of Withanolide A in targeting both α-amylase and α-glucosidase in comparison to the synthetic drug Acarbose. Protein-ligand interactions, binding affinity, and stability were characterized using pharmacological profiling, high-end molecular docking, and molecular-dynamic simulation. Withanolide A inhibited the activity of α-glucosidase and α-amylase better, exhibiting good pharmacokinetic properties, absorption, and metabolism. Also, Withanolide A was minimally toxic, with higher bioavailability. Interestingly, Withanolide A bonded well to the active site of α-amylase and α-glucosidase, yielding the lowest binding free energy of -82.144 ± 10.671 kcal/mol and -102.1043 ± 11.231 kcal/mol compared to the Acarbose-enzyme complexes (-63.220 ± 13.283 kcal/mol and -82.148 ± 10.671 kcal/mol). Hence, the findings supported the therapeutic potential of Withanolide A as α-amylase and α-glucosidase inhibitor for DM treatment.Communicated by Ramaswamy H. Sarma.